Trans-formed identity: Catherine Malabou's reading of Hegel - Ferez, Cecilia Abdo (Revista Eletrônica Estudos Hegelianos, 2022)
The article reviews Catherine Malabou's interpretation of Hegel, as a deconstruction of the metaphysics of presence and a discussion with gender theories, which disregard the body. The body appears in her interpretation as form and the Subject, as necessary alienation, as trans-formation of the body. There is a preeminence of plasticity over ontology. If the body is the place where the irreducible alienation of subjective experience is experienced, and if this alienation is not resolved in a static identity of me and you, of an ipseity and an intersubjectivity, the body is the setting in forms that are not fixed instances, but that are preserved and lost or even exploded.